Digital diplomacy : theory and practice - Bjola, Corneliu; Holmes, Marcus
"This book analyses digital diplomacy as a form of change management in international politics. The objective of the book is to theorize what digital diplomacy is, assess its relationship to traditional forms of diplomacy, examine the latent power dynamics inherent in digital diplomacy, and assess the conditions under which digital diplomacy informs, regulates, or constrains foreign policy. Organized around a common theme of investigating digital diplomacy as a form of change management in the international system, it combines diverse theoretical, empirical, and policy-oriented chapters centered on international change. This book will be of much interest to students of diplomatic studies, public diplomacy, foreign policy, social media and international relations"-- Provided by publisher